THE EFFECT OF WEIGHT TRAINING METHOD AND ARM MUSCLE POWER ON THE RESULT OF DISTANT THROW-IN WITHOUT BEGINNING OF YATPI GODONG EXTRACURRICULAR - Kasmudi, Udin; Nasuka, Nasuka; Rumini, Rumini (Journal of Physical Education and Sports, 2020)
Throw in is a way to start the match again by throwing it into the field. This study aims to determine the difference in effect between weight training methods and arm muscle power to the results of the far throw-in without the start of YATPI Godong extracurricular participants. This research uses a quasi-experimental method with a 2x2 factorial design. The sampling technique used was purposive random sampling, which was taken by 20 players. Data analysis techniques in this study using ANOVA. Based on the results of the study, weight training (sig value 0.000 < 0.050), the arm muscle power variable obtained sig value 0.255 > 0.050. In the variable type of arm muscle power training (interaction) obtained a sig value of 0.500 > 0.050. From the results of this study, that is, the method of arm muscle weight training affects the throw-in; there is no difference in the arm muscle strength of the throw-in. There is no interaction between weight training methods with arm muscle power in influencing the throw-in. Conclusion there is no interaction between weight training methods with arm muscle power in influencing the throw-in without the start of YATPI Godong extracurricular participants. Suggestions for YATPI Godong football extracurricular players, physical conditions need to be considered for achieving optimal results and need to develop more effective and appropriate training programs.